NILAI ETIKA DAN NILAI RELIGI SENIPERTUNJUKAN TAYUB DI MASYARAKAT SAMIN KABUPATEN BLORA - , FARISA AFIP WIRYATMO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Samin society is part of societies in Blora Regency. Similar to other common Blora societiesâ tradition, Samin society has the same tradition to engage tayub performance art in their lives. Samin society habit, which does not like festive things (entertainment), uses tayub as a device of tegas desa ritual ceremony has made a reason why this research is important to do. It was to investigate 1) how the form of ethical value of tayub performance of Samin society in Blora regency was, and 2) how the form of religious value of tayub performance of Samin society in Blora regency was. This research used qualitative method to explore all field data. The data collection was processed and written using descriptive analysis method applying ethnochoreology approach. Object of this research was all Samin society living in Blora Regency spread to some areas including: Ploso Kediren village, Klopoduwur village, Tanduran village Kedungtuban sub-district, and Bapangan Menden village. Tayub performance was held to give place for expression of Samin society towards a belief of a joged figure as reincarnation of god sent to the earth. An attempt to assemble universe and the self of Samin society could be materialized through some rituals such as holding village alms containing resik luwur ritual, ater-ater ritual, slametan ritual, and rayahan ritual. These offerings later ended their ritual deeds by holding ancestors or their village danyang watchperson offerings through Tayub performance. Social ethical value containing on Tayub performance art in Samin community could be seen on the attitude and behavior on performing the art and implementing the belief. Religious value in this Tayub performance was realized on a form of magical sympathetic deed activity, the day election of holding ceremony, selection of feast as offerings, madya and maithuna, deciding a number of joged(s).Ritual and other mystical deeds done by Samin society was a representation of their efforts to get inner satisfaction of their attempts to balance the universe and its contents.